2019
DOI: 10.18203/2320-1770.ijrcog20193567
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of buccal versus vaginal misoprostol in first trimester induced abortion

Abstract: Background: To compare the effectiveness, side effects, and patient satisfaction of buccal versus vaginal misoprostol administration in first trimester abortions.Methods: Women opting for first trimester abortion received oral Mifepristone followed 48 hours latermisoprostol. Group A received Misoprostol via buccal route whereas group B received Misoprostol vaginally. A comparative analysis using SPSS was done.Results: Giving 800µg Misoprostol by either buccal or vaginal route after oral Mifepristone have compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…There was no significant difference between the two study groups with respect to induction to abortion time. Overall mean induction to abortion time in buccal group was 13.15±4.01 hours as compared to 13.16±4.14 hours in vaginal group which was comparable to that reported by Khan et al 13 While et al reported induction to abortion time to be significantly longer in buccal group (40±29 hours) as compared to present study. 14 However, we found complete abortion rate to be significantly higher in buccal (88%) as compared to vaginal group (75%) while in Khan et al 13 They reported higher complete abortion rate in both buccal (96%) as well as in vaginal (98%) group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was no significant difference between the two study groups with respect to induction to abortion time. Overall mean induction to abortion time in buccal group was 13.15±4.01 hours as compared to 13.16±4.14 hours in vaginal group which was comparable to that reported by Khan et al 13 While et al reported induction to abortion time to be significantly longer in buccal group (40±29 hours) as compared to present study. 14 However, we found complete abortion rate to be significantly higher in buccal (88%) as compared to vaginal group (75%) while in Khan et al 13 They reported higher complete abortion rate in both buccal (96%) as well as in vaginal (98%) group.…”
Section: Discussionsupporting
confidence: 85%
“…Overall mean induction to abortion time in buccal group was 13.15±4.01 hours as compared to 13.16±4.14 hours in vaginal group which was comparable to that reported by Khan et al 13 While et al reported induction to abortion time to be significantly longer in buccal group (40±29 hours) as compared to present study. 14 However, we found complete abortion rate to be significantly higher in buccal (88%) as compared to vaginal group (75%) while in Khan et al 13 They reported higher complete abortion rate in both buccal (96%) as well as in vaginal (98%) group. Young et al found that buccal administration of misoprostol resulted in higher success rate before 64 days of gestation whereas vaginal misoprostol had a higher success rate through 70 days of gestation.…”
Section: Discussionsupporting
confidence: 85%